2015
DOI: 10.1108/el-05-2013-0085
|View full text |Cite
|
Sign up to set email alerts
|

Information literacy of students as a correlate of their use of electronic resources in university libraries in Nigeria

Abstract: Purpose – The purpose of this paper is to determine the relationship existing between undergraduate students’ information literacy skills and their use of electronic resources (ERs) located in university libraries in Nigeria. Design/methodology/approach – The descriptive design was adopted for the research questions, while the correlational design was adopted for the hypothesis. The purposive sampling technique was also adopted in select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 7 publications
1
28
0
1
Order By: Relevance
“…Academic libraries all over the world are experiencing a paradigm shift in acquiring, storing and retrieving information, because of the application of information communication technologies (ICTs). Libraries organised with ICTs can offer friendlier information retrieval services to users [15,20,21]. In the current technology-rich educational environment, most of the information is stored and retrieved with the help of online databases.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Academic libraries all over the world are experiencing a paradigm shift in acquiring, storing and retrieving information, because of the application of information communication technologies (ICTs). Libraries organised with ICTs can offer friendlier information retrieval services to users [15,20,21]. In the current technology-rich educational environment, most of the information is stored and retrieved with the help of online databases.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…The analyzed literature devoted the most attention to the effective use of these resources which requires from users appropriate skills and knowledge. Confirmation of these intuitively obvious statement can be found in literature: Ukachi (2015) has shown that limited digital competence of users has a direct impact on the low usage of electronic resources, Tang and Tseng (2013) confirmed the same in regard to a user's limited conviction about his effectiveness in information retrieval while Nemati-Anaraki and Babalhavaeji (2013) demonstrated a connection with a lack of knowledge about resources.…”
Section: Electronic Resourcesmentioning
confidence: 58%
“…Based on the literature, utilization of WBIS is the identified dependent variable, predicted to have relationship with three (3) independent variables consisting of library technology, academic library roles, and library learning environment. Significantly, information literacy is introduced as a moderating factor in order to gain understanding, to what extent, it has a significant relationship with the independent variables in affecting utilization of WBIS [8].…”
Section: Research Backgroundmentioning
confidence: 99%
“…Having access to sophisticated technology and electronic devices without properly equipped with information literacy skills does not assure students' ability to utilize WBIS [19]. This indicates that information literacy can play a moderating role between library technology and the utilization of WBIS, which lacking these skills will cause them not knowing how to search, compare and utilize digital resources in libraries [8]. Essentially, in a study held on the rural residents in Taiwan found that information literacy skills as a moderating role in adopting ICT [20].…”
Section: Information Literacy Skills Factormentioning
confidence: 99%
See 1 more Smart Citation